Bacterial Immunogenicity Is Critical for the Induction of Regulatory B Cells in Suppressing Inflammatory Immune Responses - Maerz, Jan Kevin; Trostel, Constanze; Lange, Anna; Parusel, Raphael; Michaelis, Lena; Schäfer, Andrea; Yao, Hans; Löw, Hanna-Christine; Frick, Julia-Stefanie (Frontiers in Immunology, 2020)
B cells fulfill multifaceted functions that influence immune responses in health and disease. In autoimmune diseases such as inflammatory bowel disease, multiple sclerosis and rheumatoid arthritis, depletion of functional B cells results in an aggravation of disease in humans and respective mouse models. This could be due to a lack of a pivotal B cell subpopulation: regulatory B cells (Bregs). Although Bregs represent only a small proportion of all immune cells, they exhibit critical properties in regulating immune responses, thus contributing to the maintenance of immune homeostasis in healthy individuals. In this study, we report that the induction of Bregs is differentially triggered by the immunogenicity of the host’s microbiota. In comparative experiments with low immunogenic Bacteroides vulgatus and strong immunogenic Escherichia coli, we found that the induction and longevity of Bregs depend on strong Toll-like receptor activation mediated by antigens of strong immunogenic commensals. The potent B cell stimulation via E. coli led to a pronounced expression of suppressive molecules on the B cell surface and an increased production of anti-inflammatory cytokines like interleukin-10. These bacteria-primed Bregs were capable of efficiently inhibiting the maturation and function of dendritic cells (DCs), preventing the proliferation and polarization of T helper (Th)1 and Th17 cells while simultaneously promoting Th2 cell differentiation in vitro. In addition, Bregs facilitated the development of regulatory T cells (Tregs) resulting in a feedback cooperation to establish immune homeostasis. Moreover, the colonization of germfree wild type mice with E. coli but not B. vulgatus significantly reduced intestinal inflammatory processes in dextran sulfate sodium (DSS)-induced colitis associated with an increase induction of immune suppressive Bregs. The quantity of Bregs directly correlated with the severity of inflammation. These findings may provide new insights and therapeutic approaches for B cell-controlled treatments of microbiota-driven autoimmune disease.